Relationship between Partial Uterine Cervical Tissue Excision and Preterm Birth: An Experimental Animal Study - Ahn, Ki Hoon; Jeong, Hyun Chul; Kim, Hee-youn; Kang, Dahyun; Hong, Soon-Cheol; Cho, Geum Joon; Oh, Min-Jeong; Kim, Hai-Joong (American Journal of Perinatology, 2017)
Objective To investigate whether the uterine cervix excision is associated with preterm birth in female mice.Study Design Sexually mature female C57BL/6 mice (n = 40) were randomly divided into four groups (A, sham; B, cervical excision; C, lipopolysaccharide, 100 µg intrauterine injection; and D, cervical excision + lipopolysaccharide injection), with 10 mice per group. Three weeks after cervical excision, timed mating was performed. On gestational day 16, lipopolysaccharide was injected between the first and second horns of the right uterus near the cervix. The uterine cervix was obtained after delivery and was histologically analyzed.Results The mean gestational period in group D was significantly lower than those in the other groups (17, 19.5, 19, and 18.2 days in groups D, A, B, and C, respectively; p = 0.034). The cervical length was shorter in the cervical excision groups (p = 0.004). The muscle-to-collagen ratio in the proximal cervix was higher in group D (p = 0.037).Conclusion Prepregnancy cervical excision and subsequent lipopolysaccharide injection showed a high rate of preterm birth, which was higher than the known lipopolysaccharide injection related preterm birth rate. Prepregnancy cervical excision appears to have additive effects with inflammation in inducing preterm birth, which are associated with the relative muscular component amount.
Keywords: uterine cervix; excision; infection; preterm birth; mouse model